3-Homoacyl coumarin: an all carbon 1, 3-dipole for enantioselective concerted (3+2) cycloaddition. Issue 90 (29th October 2018) - Chen, Yi-Ru; Ganapuram, Madhusudhan Reddy; Hsieh, Kai-Hong; Chen, Kai-Han; Karanam, Praneeth; Vagh, Sandip Sambhaji; Liou, Yan-Cheng; Lin, Wenwei
Abstract : A stereoselective concerted (3+2) cycloaddition is demonstrated from 3-homoacyl coumarins and alkylidene indandiones, resulting in fused spirocyclopentanes bearing four contiguous stereocenters. Abstract : A new type of all-carbon 1, 3-dipole precursor, 3-homoacylcoumarin, was employed for the stereoselective (3+2) cycloaddition with indandione alkylidenes to generate a series of coumarin/indandione-fused spirocyclopentanes bearing four contiguous stereogenic centers. While two reaction pathways progressed simultaneously, detailed mechanistic investigation revealed that the highly efficient stereoselective concerted route dominated the extremely slow stepwise pathway.